Identification and characterization of PlAlix, the Alix homologue from the Mediterranean sea urchin Paracentrotus lividus. (10th January 2013) - Romancino, Daniele P.; Anello, Letizia; Morici, Giovanni; d'Azzo, Alessandra; Bongiovanni, Antonella; Di Bernardo, Maria
<x xml:space="preserve">Abstract</x> The sea urchin provides a relatively simple and tractable system for analyzing the early stages of embryo development. Here, we use the sea urchin species, Paracentrotus lividus, to investigate the role of Alix in key stages of embryogenesis, namely the egg fertilization and the first cleavage division. Alix is a multifunctional protein involved in different cellular processes including endocytic membrane trafficking, filamentous (F)‐actin remodeling, and cytokinesis. Alix homologues have been identified in different metazoans; in these organisms, Alix is involved in oogenesis and in determination/differentiation events during embryo development. Herein, we describe the identification of the sea urchin homologue of Alix, PlAlix. The deduced amino acid sequence shows that Alix is highly conserved in sea urchins. Accordingly, we detect the PlAlix protein cross‐reacting with monoclonal Alix antibodies in extracts from P. lividus, at different developmental stages. Focusing on the role of PlAlix during early embryogenesis we found that PlAlix is a maternal protein that is expressed at increasingly higher levels from fertilization to the 2‐cell stage embryo. In sea urchin eggs, PlAlix localizes throughout the cytoplasm with a punctuated pattern and, soon after fertilization, accumulates in larger puncta in the cytosol, and in microvilli‐like protrusions. Together our data show that PlAlix is structurally conserved from sea urchin to mammals and may open new lines of inquiry into the role of Alix during the early stages of embryo development.